Operando X-Ray Spectroscopic Techniques: A Focus on Hydrogen and Oxygen Evolution Reactions - V, Varsha M.; Nageswaran, Gomathi (Frontiers in Chemistry, 2020)
The study of structural as well as chemical properties of an electrocatalyst in its reaction environment is a challenge in electrocatalysis. This is very important for the better understanding of the dynamic changes in the reactivity with respect to the structure of catalysts to give insight into the reaction mechanism. The in situ/operando investigation of electrode/electrolyte interface has been increasingly explored in recent days due to the significant developments in technology. The review focus on operando X-ray spectroscopic techniques to understand the behavior of electrocatalysts in hydrogen evolution and oxygen evolution reactions (HER and OER). Some recent studies on the application of operando X-ray spectroscopic methods to study the dynamic nature as well as the evaluation of structural and chemical changes of the electrocatalysts for HER and OER in different reaction environment are discussed.